An Analysis of Grammatical Errors Made by the Students of English Literature Department - Maftukhin Maftukhin (Universitas Ahmad Dahlan, 2023)
This research aims to identify grammatical errors made by the students of the English Literature department of Universitas Ahmad Dahlan and to describe the process of the occurrence of grammatical errors. This research is a descriptive study that uses a qualitative method. The data are the writing assignments of second-semester students of the English Literature department of Universitas Ahmad Dahlan of the 2018 - 2019 academic year. The researcher read the writings of the students, then wrote and classified the errors made by the students into types of errors due to interlingual and intralingual transfers. This research uses the descriptive analysis method to describe the types of errors. The results show that the types of errors due to the interlingual and intralingual transfer are omission errors, addition errors, misordering errors, and misformation errors. The results of this study are expected to be the basis for minimizing grammatical errors in the English teaching and learning process, especially for writing in English. The results can also be used as a basis for compiling course materials, writing textbooks or modules, especially for making exercises that focus on errors that often occur, to prevent similar errors that will occur in the future.